Spatial matter density mapping of the STAGES Abell A901/2 supercluster field with 3D lensing - Simon, P; Heymans, C; Schrabback, T; Taylor, A; Gray, M; van Waerbeke, L; Wolf, C; Bacon, D; Barden, M; Boehm, A; Haeussler, B; Jahnke, K; et al. (2012)
We present weak lensing data from the Hubble Space Telescope(HST)/Space Telescope A901/902 Galaxy Evolution Survey (STAGES) survey to study the three-dimensional spatial distribution of matter and galaxies in the Abell 901/902 supercluster complex. Our method improves over the existing 3D lensing mapping techniques by calibrating and removing redshift bias and accounting for the effects of the radial elongation of 3D structures. We also include the first detailed noise analysis of a 3D lensing map, showing that even with deep HST-quality data, only the most massive structures, for example M200≳ 1015M⊙h-1 at z∼ 0.8, can be resolved in 3D with any reasonable redshift accuracy (Δz≈ 0.15). We compare the lensing map to the stellar mass distribution and find luminous counterparts for all mass peaks detected with a peak significance >3σ. We see structures in and behind the z= 0.165 foreground supercluster, finding structure directly behind the A901b cluster at z∼ 0.6 and also behind the south-west (SW) group at z∼ 0.7. This 3D structure viewed in projection has no significant impact on recent mass estimates of A901b or the SW group components SWa and SWb. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.